(untitled) (Faridpur Medical College Journal, 2016)
Computer Vision Syndrome (CVS) is a condition in which a person experience one or more of eye symptoms and/or headache and back pain as a result of prolonged working on a computer. Bankers, account section workers, professional computer workers, excessive near work by mobile, laptop or tab users are commonly affected. Headache, eye strain, dryness, burning, grittiness, heaviness or watering, stiff shoulders, low back pain and general fatigue are main symptoms. The duration of computer work is directly related to eye symptoms; and longer duration tends to result in long-lasting complaints even after the work is finished. Professional workers should practice preventive measure. Correction of refractive errors, modification of work station, using antiglare screen filter and hourly eye exercise are the chief preventive strategy. Neglected person may have less/decreased working capacity and reduced productivity. Faridpur Med. Coll. J. Jan 2015;10(1): 33-35